(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores compound sentence theory, focusing on its structural and semantic classifications. It begins with a definition of compound sentences, emphasizing their role in combining independent clauses using coordinating conjunctions or punctuation. The structural types discussed include coordination through conjunctions, punctuation-only connections, asyndetic coordination, and polysyndetic coordination. Semantically, the article categorizes compound sentences based on relationships such as additive, adversative, causal, alternative, conditional, and temporal. Through examples and explanations, the article demonstrates how compound sentences enrich communication by expressing complex ideas and nuanced relationships. It highlights their importance in linguistic theory, language teaching, and practical applications like natural language processing and literary analysis. The discussion underscores the centrality of compound sentences in understanding language structure and meaning, offering insights into their theoretical and practical significance.